Longitudinal Effects of Adolescent Abuse on Relationship Quality and Posttraumatic Stress Symptoms in Mother–Adolescent Dyads. (10th December 2019) - Fitzgerald, Michael; Ledermann, Thomas
Abstract : The current study examined dyadic reports of mother–adolescent relationship quality (RQ) as a mechanism by which emotional, physical, and sexual abuse affect posttraumatic stress symptoms (PTSS) over time from a family systems perspective. We used three waves of data from the Longitudinal Studies of Child Abuse and Neglect (LONGSCAN), including 321 mother–adolescent dyads observed when adolescents were approximately 12, 14, and 16 years old. We used an extended version of the actor–partner interdependence mediation model to analyze the effect of emotional, physical, and sexual abuse on adolescents' PTSS through dyadic reports of mother–adolescent RQ. Results yielded significant indirect effects between sexual and emotional abuse, but not physical abuse, and PTSS 4 years later through adolescent perceptions of RQ. Maternal perceptions of RQ were not directly associated with adolescents' PTSS; however, maternal perceptions of RQ positively contributed to future adolescent perceptions of RQ. Clinical implications are discussed.